Designing next generation middleware for context-aware ubiquitous and pervasive computing. (13th February 2007) - Roussaki, Ioanna G.; Strimpakou, Maria A.; Anagnostou, Miltiades E.
Ubiquitous computing systems that strive to be minimally intrusive and exhibit inherent pro-activeness and dynamic adaptability to the user preferences and environment need to be context-aware. Context Awareness (CA) has the potential to greatly alleviate the human attention and interaction bottlenecks, increase the service flexibility and support intelligent personalisation and adaptability features. This paper has sprung out from the work in Daidalos IST Integrated Project on the development of a ubiquitous and pervasive service provisioning platform. This platform is based on a robust context-aware environment that aims to advance the vision of Ambient Intelligence (AmI) toward technical and economic viability.